Análise comparativa entre os sistemas de escalas para violino de Carl Flesch, Ivan Galamian e Simon Fischer. - Dantas, Paula Ferreira (2015)
Various compositions and violin musical creations were developed with the tonal system and diatonic scale. And many musical contemporary works are like construction tools that favor the technical standard learning and giving considerable importance to scale studies. Currently, the execution of musical works is to get into music courses in schools, conservatories and universities. Considering this, the present study intended to make a descriptive, comparative and reflective analysis of the scale systems of violin from Carl Flesch (1926), Ivan Galamian (1985) and Simon Fischer (2012), checking their main characteristics, similarities and differences of approach and the design of teaching methodology. The above-mentioned authors´s works exercised and still influence on practice and on the technique of violinists generations. So the intention of the present work is, with the bibliographical, exploratory and descriptive research, to help the student with his contact to the scale systems, promoting an access to educational content and the study proposals. In order to facilitate the contact of student with the various types of technical approaches and points of view, we identify similarities and differences in relation with the left hand as fingerings, position changes, chromatic scales, double stops, "broken" thirds , arpeggios, tenths, octaves, articulations and the challenges of the right hand, on the subject of sound production, diversity of rhythms and of bowings. With this, we question the efficiency of exercises and the real motivations led these authors to write their systems. The differences of technical approaches, styles and teaching methodologies also contribute to the clarification and understanding of the changes that occurred in the period that each method was written.